Information systems(is) for competitive intelligence (ci) in small and medium enterprises. - ATIENO DINDA, WILKISTER (kabarak university, 2016)
Information systems have emerged competitive advantage for firms Prior research has shown that very few IS to drive their performance especially This has been blamed on the overall information systems The essence of CI is to use your competitors strategy
Keywords: Information systems (IS) for competitive intelligence; small and medium enterprises